2019
DOI: 10.1074/jbc.ra119.009537
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A allows the allosteric regulation of a structural motif in the disordered domain 2 of NS5A and thereby fine-tunes HCV RNA replication

Abstract: Edited by Charles E. Samuel Implicated in numerous human diseases, intrinsically disordered proteins (IDPs) are dynamic ensembles of interconverting conformers that often contain many proline residues. Whether and how proline conformation regulates the functional aspects of IDPs remains an open question, however. Here, we studied the disordered domain 2 of nonstructural protein 5A (NS5A-D2) of hepatitis C virus (HCV). NS5A-D2 comprises a short structural motif (PW-turn) embedded in a proline-rich sequence, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 100 publications
6
17
0
Order By: Relevance
“…This displacement is accompanied by a decrease in linewidth and an increase in signal intensity. This indicates that the speed of interconversion between the two states is modified at high pH, and becomes slower in NMR intermediate exchange timescale (μs-ms) [52,53,69], as we have previously suggested based on NMR spin relaxation experiments [31].…”
Section: The Two Disulfide Bridges Are In Regions With Distinct Structural Properties In Isolated Cp12oxsupporting
confidence: 71%
See 1 more Smart Citation
“…This displacement is accompanied by a decrease in linewidth and an increase in signal intensity. This indicates that the speed of interconversion between the two states is modified at high pH, and becomes slower in NMR intermediate exchange timescale (μs-ms) [52,53,69], as we have previously suggested based on NMR spin relaxation experiments [31].…”
Section: The Two Disulfide Bridges Are In Regions With Distinct Structural Properties In Isolated Cp12oxsupporting
confidence: 71%
“…Interestingly, the difference in frequency between these two resonances assigned to the same proton decreased at high temperature, and this relates to an increase in intensity (and decrease in linewidth) for the folded Trp-Hε resonance (Figure 3c, Figure S5). The difference in frequency also decreased at higher pH (Figure 3b), and the resulted resonances at pH 8 and 9 fell in a linear chemical shift pattern defined by the two above mentioned unfolded and folded Trp-Hε resonances [52,53]. This behavior is strongly indicative of a chemical exchange in the intermediate timescale (μs-100 ms) between a disordered and a folded conformation, that becomes faster at higher temperature and at higher pH [54].…”
Section: Structural Transition Of the Region Encompassing The C23-c31 Disulfide Bridge Upon Oxidation Of The Isolated Proteinmentioning
confidence: 99%
“…The binding of CypA to a proline-rich region motif in NS5A-D2 enhances its RNA-binding properties [73]. This was corroborated by Dujardin et al in a recent study where CypA was shown to allosterically modulate the disordered NS5A-D2, regulating viral RNA replication efficiency [78]. CypA and NS5B share overlapping binding sites in NS5A-D2 [79], and Ngure et al showed that the RNA-binding region in NS5A-D2 coincides with the binding site of CypA and NS5B [80], suggesting the formation of a ternary complex between CypA, NS5A and NS5B that regulates viral RNA replication [81].…”
Section: Cyclophilins and Hcv Infectionmentioning
confidence: 63%
“…This displacement is accompanied by a decrease in linewidth and an increase in signal intensity. This indicates that the speed of interconversion between the two states is modified at high pH and becomes slower in NMR intermediate exchange timescale (μs-ms) [ 52 , 53 , 69 ], as we have previously suggested based on NMR spin relaxation experiments [ 31 ].…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, the difference in frequency between these two resonances assigned to the same proton decreased at high temperature, and this relates to an increase in intensity (and decrease in linewidth) for the folded Trp-Hε resonance ( Figure 3 c, Figure S5 ). The difference in frequency also decreased at higher pH ( Figure 3 b), and the resulting resonances at pH 8 and 9 fell in a linear chemical shift pattern defined by the two above-mentioned unfolded and folded Trp-Hε resonances [ 52 , 53 ]. This behavior is strongly indicative of a chemical exchange between a disordered and a folded conformation.…”
Section: Resultsmentioning
confidence: 99%